Asymmetric Synthesis of 2,2-Disubstituted Benzofuranones through an Organocatalytic Alkylation with Nitroallylic Acetates - Zhao, Long; Raabe, Gerhard; Enders, Dieter (Synthesis, 2019)
The asymmetric allylic alkylation of benzofuran-3(2H)-ones with nitroallylic acetates has been achieved employing a bifunctional thiourea organocatalyst via SN2′ substitution. A series of 2,2-disubstituted benzofuranones bearing adjacent tetrasubstituted and tertiary stereocenters have been synthesized with moderate to good yields and very good stereoselectivities.
Keywords: allylic alkylation; benzofuranones; nitroallylic acetates; organocatalysis; asymmetric synthesis